The Relationship of Risky Online Behaviors and Adverse Childhood Experiences to Online Sexual Victimization Among Korean Female Adolescents - Choi, Jungtae (Journal of interpersonal violence, 2023)
Prior research has demonstrated that online sexual victimization (OSV) is a significant social problem and is associated with adolescents’ negative developmental outcomes. However, it remains unclear whether adolescents’ risky online behaviors and offline victimization are related to the risk of OSV. The present study examined whether female adolescents’ risky online behaviors (mood regulation through the Internet, ingratiating behavior, disclosure of personal information, harassing behavior, talking with someone met online, and sexual behavior) and offline victimization (adverse childhood experiences [ACEs]) would be associated with OSV. This study recruited female adolescents and their mothers within six metropolitan cities and provinces of residential areas of South Korea. A total of 509 female adolescents participated in the survey (aged 13–18 years). The present study employed multivariate regression to examine the relationship of risky online behaviors and offline victimization to the experience of OSV. Female adolescents’ risky online behaviors (harassing behavior, talking with someone met online, and sexual behavior) were significantly associated with OSV, and those with high exposure to maltreatment and family dysfunction during childhood were more at risk of OSV than adolescents with low exposure to ACEs. The results suggest that it is important to address the effects of risky online behaviors and exposure to offline victimization on female adolescents’ sexual victimization online. Identifying risky online behaviors and offline victimization related to OSV can help researchers and practitioners further understand female adolescents’ online victimizations in the context of offline and online dynamics.